CD74 and CD44 Expression on CTCs in cancer patients with brain metastasis - Loreth, Desirée; Schütte, Moritz; Zinke, Jenny; Mohme, Malte; Piffkó, András; Schneegans, Svenja; Stadler, Julia; Janning, Melanie; Loges, Sonja; Joosse, Simon A.; Lamszus, Katrin; Westphal, Manfred; et al. (International journal of molecular sciences, 2021)
Up to 40% of advance lung, melanoma and breast cancer patients suffer from brain metastases (BM) with increasing incidence. Here, we assessed whether circulating tumor cells (CTCs) in peripheral blood can serve as a disease surrogate, focusing on CD44 and CD74 expression as prognostic markers for BM. We show that a size-based microfluidic approach in combination with a semi-automated cell recognition system are well suited for CTC detection in BM patients and allow further characterization of tumor cells potentially derived from BM. CTCs were found in 50% (7/14) of breast cancer, 50% (9/18) of non-small cell lung cancer (NSCLC) and 36% (4/11) of melanoma patients. The next-generation sequencing (NGS) analysis of nine single CTCs from one breast cancer patient revealed three different CNV profile groups as well as a resistance causing ERS1 mutation. CD44 and CD74 were expressed on most CTCs and their expression was strongly correlated, whereas matched breast cancer BM tissues were much less frequently expressing CD44 and CD74 (negative in 46% and 54%, respectively). Thus, plasticity of CD44 and CD74 expression during trafficking of CTCs in the circulation might be the result of adaptation strategies.
Published: 29 June 2021
Gesehen am 20.06.2022